Tablet‐based AR technology: Impacts on students' conceptions and approaches to learning mathematics according to their self‐efficacy. (19th November 2018) - Cai, Su; Liu, Enrui; Yang, Yang; Liang, Jyh‐Chong
Abstract: Most studies of Augmented Reality (AR) in education have considered students' learning outcomes and motivation. Previous studies have revealed that AR has the potential to help students learn abstract conceptions in mathematics. In this paper, a series of statistics and probability lessons using AR installed on tablets was designed and developed to examine the effect of the AR technology by comparing the conceptions and learning approaches of junior high school students with different levels of self‐efficacy. A total of 101 students were divided into two groups based on their mathematics learning self‐efficacy. The analysis of the results shows that AR applications in mathematics courses can help students with higher self‐efficacy to pay closer attention to higher level conceptions. It can also help higher self‐efficacy students to apply more advanced strategies when learning mathematics.